2007
DOI: 10.1063/1.2753567
|View full text |Cite
|
Sign up to set email alerts
|

Field emission of silicon emitter arrays coated with sol-gel (Ba0.65Sr0.35)1−xLaxTiO3 thin films

Abstract: ( Ba 0.65 Sr 0.35 ) 1 − x La x TiO 3 (BSLT) thin films with different La concentrations have been deposited on Si field emitter arrays (FEAs) using sol-gel technology for field electron emission applications. The films exhibit the perovskite structure at low La substitution level (x≤0.5) and the pyrochlore phase at high La concentration (x≥0.75). The 30-nm-thick BSLT (x=0.25) thin film has higher crystallinity of perovskite structure in the surface region. An x-ray photoelectron spectroscopy study indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Together with the low turn-on field and high current density described above, the current Au/Si-NC core-shells can be regarded as excellent field emitters and should be of great potential for various field emissionassociated applications. Compared to the field emission characteristics collected from the literature reported for varieties of Si-related nanostructures (Table 1), 6,[18][19][20]23 it is evident that the Pt/Si-NC and Au/Si-NC structures presented in this study outperform most of them by a large margin, except for the very low turn-on field observed in ZnO/Si-NPs. 20 However, it is noted here that in the ZnO/Si-NPs 20 the average tip radius of the Si-NPs was only about 15 nm compared to B30 nm in the present case.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Together with the low turn-on field and high current density described above, the current Au/Si-NC core-shells can be regarded as excellent field emitters and should be of great potential for various field emissionassociated applications. Compared to the field emission characteristics collected from the literature reported for varieties of Si-related nanostructures (Table 1), 6,[18][19][20]23 it is evident that the Pt/Si-NC and Au/Si-NC structures presented in this study outperform most of them by a large margin, except for the very low turn-on field observed in ZnO/Si-NPs. 20 However, it is noted here that in the ZnO/Si-NPs 20 the average tip radius of the Si-NPs was only about 15 nm compared to B30 nm in the present case.…”
Section: Resultsmentioning
confidence: 46%
“…In order to improve the field emission properties of Si-NSs, various approaches were developed. [7][8][9][10][11][12][13][14][15][16][17] For instance, various ferroelectric oxides 18,19 have been coated on the pre-fabricated Si-NSs in trying to take the advantage of low electron affinity and polarization induced electric fields at the interface, both are conceived to be beneficial to electron emissions. Alternatively, semiconductor thin films grown by atomic layer deposition (ALD) 20 were coated onto the Si-NSs to improve their field emission characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, published articles have suggested that field emission can be affected by electron affinity, 13 stoichiometric composition, 29 internal polarization strength, 30 interface structure, 31 and ferroelectric grain structure. It is likely that there are many variables impacting electron ejection from these complex materials into vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…Previous articles have reported silicon tip emitter arrays with turn-on electric fields of 13.3-70 V/lm (Refs. 30,31 There is a lack of published data on field emission from microfabricated cathodes that use epitaxial PZT, and it is not known how PZT stoichiometry affects electron emission. 13,29 The lowest reported turn-on field for a silicon tip coated with a ferroelectric film is 4 V/lm from Ba 0.67 Sr 0.33 TiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to sol-gel process, sputtering is believed to suppress the formation of the interface layer between the silicon substrate and the ferroelectric thin film. 15 In the sputtering process, the microstructure, surface energy, optical band gap, and chemical composition of the thin films are sensitive to the deposition parameters such as substrate temperature ͑T S ͒, the sputtering pressure, and the content of sputtering gases. 16,17 Therefore, the FE properties of coated ferroelectric thin film on silicon tip arrays would be affected.…”
Section: Introductionmentioning
confidence: 99%